Modernization of Indonesian Islamic Education: The Muhammadiyah Experience - Imran Ariadin; Syahril Rambe (Edumaspul: Jurnal Pendidikan, 2022)
Writing this article aims to find out about the modernization of Indonesian Islamic education: the Muhammadiyah experience. The method used in conducting this research is descriptive qualitative with a literature study approach with content analysis. The findings can be explained as follows: 1) Muhammadiyah's educational reform philosophy is based on the thoughts of its founder, KH Ahmad Dahlan. His ideas and ideas that prompted him to modernize education were integrating general-religious scholarship and adopting two Western education systems-Islamic boarding schools. This thought later became Muhammadiyah's philosophy in managing and developing Islamic educational institutions under its guidance. The typology of renewal is modernist thought. 2) Aspects of modernizing Muhammadiyah education include goals, curriculum, methods, human resources and educational institutions. Each of these five aspects has renewals starting from educational goals that are always relevant to the development of the times but still adhere to the Qur'an and Hadith. The curriculum and methods are no longer guided by the classical system and adopt the Western curriculum without eliminating religious education. So that human resources and institutions are managed properly in accordance with the development of science and technology, 3) The contribution of education initiated by Muhammadiyah is very large in educating the life of the nation. Muhammadiyah has participated in the organization of education since 1911 until now. A total of 6,555 Muhammadiyah educational institutions have contributed to the implementation and development of national education. So it is not surprising that Muhammadiyah educational institutions have survived because of their flexibility with the times.